Probability and Mechanics of Ship Collision and Grounding - Zhang, Shengming (Elsevier Ltd. : Butterworth-Heinemann, 2019)
Probability and Mechanics of Ship Collision and Grounding provides simplified analytical procedures for ship collision and grounding assessments, including probabilistic methods, an estimation of the energy released during collisions, and a prediction of the extent of damage on involved structures. An additional chapter is dedicated to current finite element analysis techniques that are used for estimating structural damage during ship collisions. The book encapsulates reliable and fast analysis methods for collision and grounding assessment, presenting tactics that have been extensively validated with experimental and numerical results. In addition, all described analysis methods include realistic calculation examples to provide confidence in their use.
Keywords: Collisions at sea -- Prevention.; Stranding of ships -- Prevention.; Navigation -- Safety measures.; elektronické knihy; electronic books